Cytotoxic Activity and Senescence Modulatory Effect of Hesperetin on Triple-Negative Breast Cancer Cells and Kidney Cells Co-Treatment with Cisplatin - Artanti, Anif Nur; Jenie, Riris Istighfari; Rumiyati, Rumiyati; Meiyanto, Edy (Indonesian Society for Cancer Chemoprevention, 2023)
Cisplatin (Cisp) is a non-specific chemotherapeutic agent for breast cancer. Hesperetin (HST), a flavanone found in various citrus fruits, exhibits bioactive properties, functioning as an antioxidant, anti-inflammatory, and anticancer agent. The objective of this research was to investigate the potential of HST as a co-chemotherapeutic agent in conjunction with Cisp, specifically focusing on its cytotoxic effects against 4T1 triple-negative breast cancer cells and senescence modulatory effect on Vero normal kidney cells. The cytotoxic effect and viability cell of HST were evaluated through 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium (MTT) assay. In addition, the effect of cellular senescence inhibition on the Vero cell line was measured using senescence-associated β-galactosidase (SA-β-gal) staining. In the MTT assay, both HST and cisplatin demonstrated a reduction in the viability of 4T1 cells in a dose-dependent manner, yielding IC50 values of 498 μM and 2 μM, respectively. The co-treatment of HST and cisplatin showed an increase in sensitivity of the 4T1 cells with a combination index of <1. HST showed low cytotoxic activity against Vero cells, with IC50 values of over 500 μM. HST decreased cellular senescence induced by cisplatin exposure on Vero cells. These results indicated that HST in co-treatment with cisplatin decreased 4T1 cell viability synergistically. HST independently reduces the cellular senescence of normal cells. Consequently, HST holds promise for potential development as a co-treatment agent in combination with cisplatin for breast cancer cells, and it may also serve as an alternative for counteracting senescence in healthy tissues.Keywords: cytotoxic, senescence, hesperetin, cisplatin, breast cancer.